Incidental finding of antiphospholipid antibody syndrome in a patient with Cor Pulmonale: A case report - Nayyab, Izzah; Bashir, Hassan; Shahbaz, Hamza (Journal of the Pakistan Medical Association, 2025)
Antiphospholipid antibody syndrome (APS), despite being an uncommon condition, displays a remarkably varied array of clinical presentations. It is a hypercoagulable disease characterised by recurrent thrombotic vascular events such as deep vein thrombosis (DVT) and pulmonary embolism. There is significant pregnancy morbidity associated with APS. Recurrent foetal loss is one of the predominant forms of presentation in women. The Sapporo classification states that there must be both clinical and laboratory findings to confirm APS. Anti-thrombotic therapy remains the mainstay of treatment. Pulmonary hypertension and right heart failure are rare complications in APS. We present the case of a 46-year-old lady diagnosed with APS and developed these rare complications. The case highlights the importance of considering APS in cases of atypical presentation with pulmonary hypertension and prior pulmonary embolism. Keywords: Antiphospholipid, Pulmonary hypertension, Cor pulmonale, Thrombosis.